Chapter First investigation of per-and poly fluoroalkylsubstances (PFAS) in striped dolphin Stenella coeruleoalba stranded along Tuscany coast (north western Mediterranean Sea) - Altemura, Paolo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Per- and poly fluoroalkylsubstances (PFAS) were measured in liver,muscle, blood and brain of 26 stripped dolphin Stenella coeruleoalba stranded along Tuscany coasts (Italy), from 2020 to 2022. Using high performance liquid chromatography coupled with high resolution mass spectrometry 18 target were quantified in each sample. PFOS, PFHxS, FOSA were found in all samples with PFOS blood concentration level ranging from some tens to some hundreds of µg/kg. The concentrations follow the trend PFOS>FOSA>PFHxS and the PFOS concentration appears to be inversely proportional to the weight of the animals.